Average number is an insufficient metric for interferometry. (22nd December 2021) - Branford, Dominic; Rubio, Jesús
Abstract: We argue that analysing schemes for metrology solely in terms of the average particle number can obscure the number of particles effectively used in informative events. For a number of states we demonstrate that, in both frequentist and Bayesian frameworks, the average number of a state can essentially be decoupled from the aspects of the total number distribution associated with any metrological advantage.